Numerical evaluation of a novel passive variable friction damper for vibration mitigation. (1st October 2020) - Barzegar, Vahid; Laflamme, Simon; Downey, Austin; Li, Meng; Hu, Chao
Highlights: Novel variable friction damper applied to wind and seismic mitigation. Probabilistic motion-based design approach proposed. Device and design methodology demonstrated numerically. Abstract: This study assesses the performance of a novel passive variable friction damper (PVFD) at mitigating wind- and seismic-induced vibrations. The PVFD consists of two friction plates upon which a cam profile modulates the normal force as a function of its rotation. A unique feature of the PVFD is its customizable shape, yielding a customizable friction hysteresis. The objective of the study is to assess the benefits of crafting the friction behavior to satisfy motion criteria. This is done numerically on two example buildings: a 5-story structure subjected to seismic loads, and a 20-story structure subjected to non-simultaneous seismic and wind loads. A probabilistic performance-based design procedure is introduced to select the optimum cam configurations throughout each building under the design loads. After that, numerical simulations are conducted to compare their performance against that of two equivalent damping schemes: viscous dampers and passive friction dampers. Results show that customization of the hysteresis behaviors throughout a structure is necessary to yield optimal performance. Also, the PVFD outperforms the other damping schemes for wind mitigation by yielding a more stable response in terms of lower accelerations over the entire wind event. Under seismic loads, all three damping schemes exhibited comparable performance, but the PVFD yielded a significantly more uniform drift for the 20-story building.